Proximity off-shoring generating considerable savings with no significant increase of risks or losses in quality: near-shoring playing a key role on a business transformation program - Guedes, J. F.; Pereira, L. (Eurasian Studies in Business and Economics, 2017)
Information Technology leaders are demonstrating an increased concern on the distance dimension while considering sourcing initiatives. This suggests that, in Information Technology outsourcing activities, “distance is not dead”—actually, distance is seen as a source of challenges that can hurt the project overall health. In order to reduce these risks keeping an effective cost, proximity offshoring (nearshoring) is getting more used over the past two decades, but the academic literature on the subject is still on its beginnings. Using an Information Technology project, part of a large business transformation program that took place in Geneva (Switzerland), done by a vendor that delivered more than 2500 days in consulting as the main case study, this paper analyzes and discusses the benefits and challenges of incorporating nearshoring practices in these types of initiatives. The analysis starts by suggesting that nearshoring can add value to Information Technology projects if managed the right way—when compared to traditional services delivery (onsite consultants), nearshoring practices can have an outstanding result, with a very positive financial impact, showing considerable savings and avoiding a significant increase of risks or losses in quality, leading to an increased return on investment (ROI). Finally, some recommendations are suggested as the starting point for a framework for nearshore usage, pointing directions for further research. A similar analysis was already published by the same authors for a training project, aiming to understand if the same trends are applicable in several types of services delivered using nearshoring practices.